2010
DOI: 10.1186/1471-2172-11-61
|View full text |Cite
|
Sign up to set email alerts
|

Differential mucosal expression of Th17-related genes between the inflamed colon and ileum of patients with inflammatory bowel disease

Abstract: BackgroundImmunological and genetic findings implicate Th17 effector cytokines in the pathogenesis of inflammatory bowel disease (IBD). Expression of Th17 pathway-associated genes is mainly studied in colonic disease. The present study assessed the mRNA expression levels of Th17 effector cytokines (IL17A, IL17F, IL21, IL22 and IL26) and genes involved in differentiation (IL6, IL1B, TGFB1, IL23A and STAT3) and recruitment of Th17 cells (CCR6 and CCL20) by quantitative real-time PCR analysis of colonic and ileal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 47 publications
3
39
1
2
Order By: Relevance
“…The use of control tissues derived from the small intestine is valid in accordance with published studies identifying the colorectal junction as a primary site of O157 colonization in the large intestines of cattle (7,36). In addition, studies have reported the use of small or large intestinal tissues of healthy individuals as controls to determine relative increases in the expression of inflammatory cytokines in human patients with inflammatory bowel disease (4).…”
Section: Discussionsupporting
confidence: 50%
“…The use of control tissues derived from the small intestine is valid in accordance with published studies identifying the colorectal junction as a primary site of O157 colonization in the large intestines of cattle (7,36). In addition, studies have reported the use of small or large intestinal tissues of healthy individuals as controls to determine relative increases in the expression of inflammatory cytokines in human patients with inflammatory bowel disease (4).…”
Section: Discussionsupporting
confidence: 50%
“…A recent study revealed ileal IBD samples have increased expression of IL17A but unchanged expression of TGFB1, IL23A, STAT3, and the Th17 recruitment factors, whereas inflamed colonic samples have increased expression of all Th17 pathway-associated genes (55). Indeed, ileal IL17A expression was elevated in DSS-positive controls but was lowered by soy peptide supplementation.…”
Section: Discussionmentioning
confidence: 96%
“…Th17 cells and/or IL-17 are detected in CD patients [35-37,44-48]. However, the generation and functional relevance of Th17 cells remains poorly understood in CD patients.…”
Section: Discussionmentioning
confidence: 99%